Peran Imam Al-Asy’ari dan Al-Maturidi Dalam Pengembangan Pemikiran Aswaja di Pendidikan Islam - Uswatun Hasanah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the contributions of Imam Abu Hasan Al-Ash'ari and Imam Abu Mansur Al-Maturidi in shaping the Ahlussunnah wal Jama'ah (Aswaja) school of thought and its implications for Islamic education. Both imams are considered foundational figures in Islamic theology, and their ideas have influenced the development of the creed (aqidah), Islamic theology (ilm al-kalam), and Islamic philosophy in various Islamic educational institutions throughout history. Through a qualitative research method with a literature review approach, this study analyzes both primary and secondary sources, including classical texts and modern interpretations, to assess the relevance of their thoughts in the context of contemporary Islamic education systems. The findings indicate that the Ash‘arite and Maturidite theological frameworks, which emphasize the balance between revelation and rationality, have been instrumental in shaping curricula, teaching methodologies, and approaches to religious understanding. The concept of moderation, or wasatiyyah, in both theological schools is central to this approach, encouraging a balanced interpretation of Islamic teachings that addresses modern challenges. The study concludes that integrating the principles of Ash‘arite and Maturidite theology into contemporary educational practices offers valuable insights into fostering a more inclusive, balanced, and rational approach to Islamic learning.